An idea of Architecture: Schools of Architecture - Tommaso Brighenti (Agathón)
In the face of the changes in recent years that have characterized world architecture and its transmissibility, this paper poses certain questions to seek an answer in the analysis of some schools of architecture which have been able to defend themselves from that liquid horizon and from those changes caused primarily by the social penetration of technologies thanks to having a strong identity and a well-defined cultural project. Four schools have been compared: the Escuela de Arquitectura y Diseño (PUCV) of Valparaíso; the Cooper Union of New York; the Faculty of Architecture of the University of Porto (FAUP); the School of Civil Architecture of the Polytechnic University of Milan-Bovisa.